INFLUENCE OF THE VARIATION OF THE PERCENTAGE OF INCREASE OF BAUXITE RESIDUE ON THE PHYSICAL AND MECHANICAL PROPERTIES OF SYNTHETIC COARSE AGGREGATES AND THEIR USE IN STRUCTURAL CONCRETE OF NORMAL STRENGTH PORTLAND CEMENT - Fernandes, Robson da Silva; de Lima, João Carlos Lisboa; Ribeiro, Marcella Camilly Dias; de Souza, Danusa Mayara; Pantoja, Lucas Miranda; Farias, Marcelo Martins; Farias, Celestina Lima de Rezende; Maia, Fabíola Thomaz; Lamarão, Wladimir Rafael de Matos; Chaves, Patricia da Silva; Santos, Elsimar Souza; Lopes, Lucas Emanoel Mateus Pereira; et al. (Seven Editora, 2026)
The present study is an integral part of an extensive cooperation project aimed at conducting research between the Federal University of Pará and the company Hydro Alunorte. The proposal consisted of producing synthetic coarse aggregates from bauxite residue (AGS) and their subsequent use in the production of conventional-strength structural concrete. This research refers to the study, which partially addressed the dynamics of the production cycles of synthesized aggregates. For this purpose, the AGS70 and AGS80 coarse aggregates from the third production cycle were used. The percentage discrepancy of residue in the aggregate composition was approximately 10%. Among the results obtained, the analyses of the physical and mechanical properties of the synthetic aggregates stand out. In this context, AGS80 showed a water absorption capacity 24% higher than that of AGS70. The results obtained in the composites with AGS70 and AGS80 aggregates indicated that, at an initial stage, the concrete with AGS80 showed better results regarding physical and mechanical properties.DOI: https://doi.org/10.56238/sevened2026.008-048